Enhancing Students' Reading Interest through Effective Library Management Implementation - Tuti Yuliana Dewi; Sulaeman Miru; Saharuddin Kaseng; Suryadi Hadi (PT. Global World Scientific, 2024)
This study aims to analyze how library management can contribute to improving students' reading interest at SD Inpres 1 Kawatuna. Based on interviews with the principal, teachers, and library managers, it was found that although the library facilities are quite adequate, the main challenge faced is the low interest of students in visiting the library. The main factors influencing the low interest in reading are the limited variety of book collections relevant to students' interests, as well as the lack of engaging literacy activities. Therefore, more creative efforts are needed to enhance literacy programs that can capture students' interest and foster better reading habits. Additionally, this study highlights the importance of integrating technology into literacy activities, such as the use of digital applications and e-books, to attract students who are more familiar with technology. Although challenges related to limited funds still exist, support from various parties, such as the government, the community, and parents, is necessary to create a conducive and attractive library environment for students. With effective library management, enhanced book collections, and engaging literacy activities, it is hoped that students' interest in reading will increase, ultimately contributing to improved education quality in Indonesia.